Modelling one-way out-of-plane response of single-leaf and cavity walls. (15th July 2018) - Tomassetti, U.; Graziotti, F.; Penna, A.; Magenes, G.
Highlights: SDOF model for analysis of one-way bending OOP dynamic behaviour of URM walls. Model captures pre/post activation mechanism response of single leaf and cavity walls. Better understanding of experimental dynamic behaviour exhibited by the specimens. Proposal of parameters to model the walls force–displacement capacity curve. Emphasis is placed on the energy dissipation involved in such mechanisms. Abstract: Existing unreinforced masonry (URM) buildings have often exhibited both damage and collapse in the out-of-plane (OOP) direction due to the activation of a local mechanism when subjected to earthquake excitations. The assessment of the out-of-plane response of masonry structures has been largely studied in the literature, typically assuming walls responding as rigid blocks or assemblies of rigid bodies. This paper presents a single-degree-of-freedom (SDOF) numerical model for the analysis of the dynamic OOP behaviour of URM walls or portion of walls. It takes into account both the linear and the non-linear rocking response phase of URM walls. The numerical model has been developed to capture the experimental dynamic response of both single leaf and cavity wall specimens subjected to a pure one-way bending action with both top and bottom end supports of the wall moving simultaneously. A detailed investigation into the force–displacement relationships characterising both wall typologies has been carried out in order to provide reliable parameters for the simulation of their dynamic behaviour. Particular emphasis is placed on the energy dissipation involved in such mechanisms. Different equivalent viscous damping models have been adopted and compared in order to identify the most appropriate one to capture the dependency of the damping phenomenon on the oscillation amplitude and subsequently the system frequency.